If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -6 = -1(6 + -1x) Reorder the terms: -6 + x = -1(6 + -1x) -6 + x = (6 * -1 + -1x * -1) -6 + x = (-6 + 1x) Add '6' to each side of the equation. -6 + 6 + x = -6 + 6 + 1x Combine like terms: -6 + 6 = 0 0 + x = -6 + 6 + 1x x = -6 + 6 + 1x Combine like terms: -6 + 6 = 0 x = 0 + 1x x = 1x Solving x = 1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. x + -1x = 1x + -1x Combine like terms: x + -1x = 0 0 = 1x + -1x Combine like terms: 1x + -1x = 0 0 = 0 Simplifying 0 = 0 The solution to this equation could not be determined.
| 5m^2+24mn+27n^2=0 | | 10t-300=p | | 5f+4(-5+3f)=1-f | | x+2+1=-4x | | -7x^2-40xy-25y^2=0 | | 40+.20x=60x | | 4x^2-20x+100=0 | | 4x^2-20x-100=0 | | x+2+1=-4 | | 3x^2+11xy-70y^2=0 | | F(x)=-4 | | 4(3b+a)= | | 2x+45+3x-20=180 | | x^2+16x+243=180 | | -2x=-35.24 | | 2x+4(y-3)=10y-8x | | 425=x+365 | | 13-x=36 | | x^3+21x+6=0 | | (ab+3a+7)-(-5ab-2)= | | x-y+2=1 | | 2y=10+4x | | -2y=3x-10 | | 5(3x-6)=4(10x+15) | | x^2+x-510=0 | | 3*x(x+3)=180*180 | | x-t+21=x-21-t | | 21-x=71-x | | x-21=x-71 | | log(X)=2.79 | | 2y-1y=0 | | XY(X^2+Y^2)=47.3 |